(untitled) (Western European Journal of Historical Events and Social Science, 2025)
Today, in the era of globalization, when geopolitical and ideological processes are intensifying, as well as in the context of increasing economic, political, national, religious, and other contradictions in the world, ensuring interethnic harmony is one of the main directions of the policy of every state. One of the urgent problems of historical science is the large-scale reforms being carried out in the Republic of Uzbekistan, including in the Republic of Karakalpakstan, in the sphere of interethnic relations, the scientific study of the activities of national cultural centers.